Boosting homogeneous chemoselective hydrogenation of olefins mediated by a bis(silylenyl)terphenyl-nickel(0) pre-catalyst. Issue 8 (14th January 2021) - Lücke, Marcel-Philip; Yao, Shenglai; Driess, Matthias
Abstract : The isolable chelating bis(N-heterocyclic silylenyl)-substituted terphenyl ligand [Si II (Terp)Si II ] as well as its bis(phosphine) analogue [P III (Terp)P III ] have been synthesised and fully characterised. Abstract : The isolable chelating bis(N-heterocyclic silylenyl)-substituted terphenyl ligand [Si II (Terp)Si II ] as well as its bis(phosphine) analogue [P III (Terp)P III ] have been synthesised and fully characterised. Their reaction with Ni(cod)2 (cod = cycloocta-1, 5-diene) affords the corresponding 16 VE nickel(0) complexes with an intramolecular η 2 -arene coordination of Ni, [E(Terp)E]Ni( η 2 -arene) (E = P III, Si II ; arene = phenylene spacer). Due to a strong cooperativity of the Si and Ni sites in H2 activation and H atom transfer, [Si II (Terp)Si II ]Ni( η 2 -arene) mediates very effectively and chemoselectively the homogeneously catalysed hydrogenation of olefins bearing functional groups at 1 bar H2 pressure and room temperature; in contrast, the bis(phosphine) analogous complex shows only poor activity. Catalytic and stoichiometric experiments revealed the important role of the η 2 -coordination of the Ni(0) site by the intramolecular phenylene with respect to the hydrogenation activity of [Si II (Terp)Si II ]Ni( η 2 -arene). The mechanism has been established by kinetic measurements, including kinetic isotope effect (KIE) and Hammet-plot correlation. With this system, the currently highest performance of a homogeneous nickel-based hydrogenation catalyst of olefins (TON = 9800, TOF = 6800 h −1 ) could be realised.